Abordagens de análise musical para música de desenhos animados: um estudo de caso do filme La Abuela Grillo - Miranda, Nebai Marteli Ríos (2023)
This paper addresses the animated short film La Abuela Grillo (2009), a Bolivian- Danish production, and, through various facets of musical analysis, seeks to explore and understand how musical concepts and sonorities of Andean cultures are used as an element that serves as an essential link between identity, emotionality, and the narrative of the story being told. To this end, the research begins with a discussion of the roles and characteristics of music in Andean cultures. Subsequently, the music and sounds of the short film are broken down into an analytical plot where concepts of harmonic/melodic analysis, electroacoustic music and audiovisual analysis are interwoven.